A nanoarchitectured cermet composite with extremely low Ni content for stable high-performance solid oxide fuel cells. (March 2021) - Park, Jung Hoon; Lee, Jong-Ho; Yoon, Kyung Joong; Kim, Hyoungchul; Ji, Ho-Il; Yang, Sungeun; Park, Sangbaek; Han, Seung Min; Son, Ji-Won
ABSTRACT: A strategy for improving the stability of nickel-based solid oxide fuel cell (SOFC) anodes via compositional and microstructural engineering is presented. Ni content was reduced to 2 vol%, and nanosized Ni particles were uniformly dispersed in a mixed ionic-electronic conducting matrix comprising gadolinium-doped ceria (GDC) using a thin-film technique. Remarkable stability with no performance deterioration even after 100 reduction-oxidation cycles could be observed for the optimized nanostructured anodes. Cell performance at 500°C was enhanced, exceeding 650 mW/cm 2 . This study offers valuable insights for enhancing the durability, performance, and productivity of SOFCs. Graphical abstracts: Image, graphical abstract